Rhodamine B pattern after whitening with peroxides and violet light: confocal laser microscopy observation - Perches, Carolina; Gobbo, Vanessa; Kury, Matheus (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
This study observed degradation pattern of Rhodamine B (RhodB) after whitening protocols with 35% hydrogen (HP) or 37% carbamide peroxide (CP) combined with violet light (VL). Bovine enamel-dentin blocks (4x4x3mm) were immersed in 30mL solution of 0.012 mM Rhodamine B (Sigma-Aldrich, St Louis, MO, USA) during seven days at 80C. Afterwards, specimens (n=3) were submitted to whitening protocols: VL/HP, HP, VL/CP, CP and VL. Following application of gels/light on enamel surface, specimens were cut tinto 1-mm slices with vegetable oil. After polishing, slices were qualativetely evaluated by Laser Scanning Confocal Fluorescence Microscopy (TCS SP5AOBS, Leica Microsystems CMS GmbH, Germany) with a wavelength of 543 ?m. Regardless of the peroxide presence, a thick layer of RhodB was preserved throughout enamel outer surface. Absence of fluorescence in the middle third of CP and HP groups indicates degradation of RhodB restricted to this area. Nevertheless, higher pattern of Rhodb degradation could be observed for groups combining CP or HP with VL. Even though VL presented a more homogenous pattern of RhodB distribution, the middle third seems to have been degraded by light irradiation. To conclude, RhodB penetrated through dental structures and it was preserved in the outer surface. However, peroxides were able to degrade it. Although light irradiation seems to have influenced RhodB patterns for CP and HP groups, violet irradiation alone did not completely degrade RhodB.